PENGARUH PDB, TINGKAT SUKU BUNGA DAN TINGKAT INFLASI TERHADAP PERMINTAAN UANG DI INDONESIA PERIODE 1999-2021 - , Rahmat Richard, Nilpa Maulidini Hrp , Anthony Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the effect of Gross Domestic Product (GDP), Interest Rates and Inflation rates on the Demand for Money in Indonesia for the 1999-2021 Period. The analytical method in this study uses secondary data which is classified as descriptive and quantitative time series data. Data analysis techniques in this study used linear regression estimation with the Error Correction Model (ECM) model, statistical tests (t test, F test, coefficient of determination R2). In connection with this problem, the following hypothesis is proposed where interest rates have a negative relationship in the short and long term to the demand for money in Indonesia in the 1999-2021 period, while the inflation rate and GDP variables have a significant positive relationship to the demand for money in the short and long term in Indonesia in the 1999-2021 period. The results of this study indicate that the interest rate variable and inflation variable have no significant effect in the short or long term on the demand for money. GDP has a positive and significant long-term influence on the demand for money in Indonesia in the 199-2021 period, but has no effect in the short term. Keywords : GDP, Interest Rate, Inflation Rate, Demand for money.